Nutritional and socio-economic predictors of adult height in 152 world populations - Grasgruber, P; Hrazdíra, E (Economics and human biology, 2020)
Height is one of the most sensitive indicators of well-being because it combines the external influences of nutrition, economic wealth, health care, social equality, and other important socio-economic factors. The aim of this ecological study was to compare actual values of male and female height from 152 populations (except sub-Saharan Africa) with the mean supply of 47 food items from the FAOSTAT database (1995-2013) and mean values of seven socio-economic indicators (1995-2013). This comparison shows that economic wealth at the country level is only a mediocre correlate of physical growth because it is only loosely associated with the quality of nutrition and it does not reflect the social distribution of wealth. In a multiple regression model, the best predictors of stature are protein sources of the best and worst quality, and total fertility (which critically influences the amount of resources expended per child). In summary, these findings indicate that irrespective of crude economic statistics, the choice of specific nutrient sources and small family size are crucial factors determining the optimal physical development of children. Based on our data, we also believe that current international dietary recommendations regarding protein intake and protein quality would deserve serious re-evaluation.
Keywords: Protein quality; dieta; Nutritional Status; mladiství; Socioeconomic Factors; Nutrition; mužské pohlaví; Body Height; Adult; mladý dospělý; socioekonomické faktory; Total fertility; Young Adult; ženské pohlaví; Humans; celosvětové zdraví; Global Health; Diet; dospělí; nutriční stav; Female; Height; Adolescent; tělesná výška; lidé; Male